2015
DOI: 10.1007/s10008-015-3047-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel La2-x Cu x NiO4±δ /La4Ni3O10-δ composite materials for intermediate temperature solid oxide fuel cells, IT-SOFC

Abstract: Phases constituted by La 2-x Cu x NiO 4±δ (0.01≤x≤ 0.1) of the Ruddlesden-Popper family (La n+1 Ni n O 3n+1 ; n=1) were prepared and then mixed with La 4 Ni 3 O 10 , in a weight ratio of 50:50 wt%, in order to be used as solid oxide fuel cell cathodes. ASR values relative to the symmetrical cells constituted by yttria-stabilized zirconia electrolyte and the following e l ec t r o d es , L a 1 . 9 8 C u 0 . 0 2 N i O 4 + δ + La 4 N i 3 O 1 0 an d La 1.95 Cu 0.05 NiO 4+δ + La 4 Ni 3 O 10 , are of 11.8 Ω cm 2 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…X-ray patterns of powders obtained after heat treatment at 1000 °C during 5 h, were recorded as reported in Fig.1. Eventually the phase obtained is pure K 2 NiF 4 -type and no secondary phases were detected, which is in agreement with the results obtained by other authors [3,24,[29][30][31] and confirmed by (JCPDS, ref. 27-1180).…”
supporting
confidence: 94%
See 2 more Smart Citations
“…X-ray patterns of powders obtained after heat treatment at 1000 °C during 5 h, were recorded as reported in Fig.1. Eventually the phase obtained is pure K 2 NiF 4 -type and no secondary phases were detected, which is in agreement with the results obtained by other authors [3,24,[29][30][31] and confirmed by (JCPDS, ref. 27-1180).…”
supporting
confidence: 94%
“…La 2-x NiO 4±δ (LXNO) with x varying between 1 % and 5 % (x = 0.01, 0.02, 0.03, 0.05) powders samples was prepared by the citrate method [3,24,29]. Starting materials were:…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, the composite is the mixture of pre-synthesized components by physically mixing, for example, ball-milling (Figure 2A). [33][34][35][36][37][38][39] However, some disadvantages, such as the inhomogeneous distribution of the different parts, large grain size, and poor stability under the harsh operational atmosphere, significantly limit the catalytic performances. Surface modification via physical deposition techniques is an effective route for getting uniform size distribution of the second component to get multifunctional composites (Figure 2B).…”
Section: Concept Of Perovskite Oxide Coupled Nanocompositesmentioning
confidence: 99%
“…Electrochemical devices, such as fuel cells that directly con-One apparent and practicable solution to overcome the drawbacks of single-phase perovskite oxide is the formation of composite electrocatalysts. [28,[33][34][35][36][37][38][39] For instance, for perovskite oxide with high ionic conductivity but lacks electronic conductivity, physically mixing another perovskite oxide with suitable electronic conductivity to form a composite is the easiest way to improve overall performance. [40][41][42] This strategy has widely been used and showed modestly improved performances of anodes or cathodes in solid oxide fuel cells (SOFCs) based on oxygen ionconducting electrolyte and protonic ceramic fuel cells (PCFCs) based on proton-conducting electrolyte, where the electrodes require both high ionic (O 2− or H + ) and electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%